The sociology of elite distinction from theoretical to comparative perspectives - Daloz, Jean-Pascal 1960- (Palgrave Macmillan, 2010)
"This major new contribution to the study of consumption examines how dominant groups express and display their sense of superiority through material and aesthetic attributes, demonstrating that differences from one society to another, and across historical periods, challenge current understandings of elite distinction"--Provided by publisher
Includes bibliographical references and index
Keywords: Elite (Social sciences); Social status; Consumption (Economics); Wealth; Sozialstatus; Verbrauch; Soziale Ungleichheit; Elite; Soziologische Theorie